Benzoyl Peroxide Formulated Polycarbophil/Carbopol 934P Hydrogel with Selective Antimicrobial Activity, Potentially Beneficial for Treatment and Prevention of Bacterial Vaginosis. (7th December 2013) - Xu, Shiqi; Cavera, Veronica L.; Rogers, Michael A.; Huang, Qingrong; Zubovskiy, Konstantin; Chikindas, Michael L.
Abstract : The human vagina is colonized by a variety of indigenous microflora; in healthy individuals the predominant bacterial genus is Lactobacillus while those with bacterial vaginosis (BV) carry a variety of anaerobic representatives of the phylum Actinobacteria . In this study, we evaluated the antimicrobial activity of benzoyl peroxide (BPO) encapsulated in a hydrogel against Gardnerella vaginalis, one of the causative agents of BV, as well as indicating its safety for healthy human lactobacilli. Herein, it is shown that in well diffusion assays G. vaginalis is inhibited at 0.01% hydrogel-encapsulated BPO and that the tested Lactobacillus spp. can tolerate concentrations of BPO up to 2.5%. In direct contact assays (cells grown in a liquid culture containing hydrogel with 1% BPO or BPO particles), we demonstrated that hydrogels loaded with 1% BPO caused 6-log reduction of G. vaginalis . Conversely, three of the tested Lactobacillus spp. were not inhibited while L. acidophilus growth was slightly delayed. The rheological properties of the hydrogel formulation were probed using oscillation frequency sweep, oscillation shear stress sweep, and shear rate sweep. This shows the gel to be suitable for vaginal application and that the encapsulation of BPO did not alter rheological properties.